2014
DOI: 10.3109/13880209.2014.908396
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effect ofBiophytum sensitivumextract on rats with acetic acid-induced ulcerative colitis

Abstract: Context: Traditionally, Biophytum sensitivum (L.) DC (Oxalidaceae) is used in Indian medicine to treat diseases include stomachache, convulsions, cramps, inflammation, and ulcer. Objective: The present study examines the effect of aerial parts of B. sensitivum (methanol extract) on a murine model of ulcerative colitis (UC). Materials and methods: UC was induced by intracolonic injection of 3% acetic acid in Wistar rats. B. sensitivum (50 or 100 mg/kg b wt) or reference drug sulfasalazine (100 mg/kg b wt) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Morphometric measurements documented a statistically significant rise in the mean area% of both iNOS and COX-2 immunostained sections of group II when compared to control. This was in accordance with Sakthivel and Guruvayoorappan, (2014) [56] and Barbosa Bezerra et al (2017) [18] . They reported that iNOS and COX-2 over expression was noted in AA induced colitis.…”
Section: Discussionsupporting
confidence: 92%
“…Morphometric measurements documented a statistically significant rise in the mean area% of both iNOS and COX-2 immunostained sections of group II when compared to control. This was in accordance with Sakthivel and Guruvayoorappan, (2014) [56] and Barbosa Bezerra et al (2017) [18] . They reported that iNOS and COX-2 over expression was noted in AA induced colitis.…”
Section: Discussionsupporting
confidence: 92%
“…53,54,55 Indeed colonic inflammation is characterized by infiltration of neutrophils that migrate to the colonic wall after aggression. These data fully corroborated previous reports, indicating that acetic acid-induced colitis is accompanied by an oxidative balance perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…These data fully corroborate previous reports, indicating that acetic acid-induced colitis is accompanied by an oxidative balance perturbation. [53][54][55] Indeed colonic inammation is characterized by the inltration of neutrophils that migrate to the colonic wall aer injury. 56 However the oxygen consumed by neutrophils is enzymatically converted to the superoxide anion (O 2 c À ) by the univalent transfer of two electrons from the cellular NADPH of the hexose monophosphate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, excessive NO production associated with increased COX-2 exacerbates ulcerative colitis. In support of this notion, Sakthivel and Guruvayoorappan (2014) demonstrated that exacerbation of acetic acid-induced colitis in rats was accompanied by increased protein expression of NOS and COX-2. Notably, evidences showed that the positive or negative effects of NO on COX-2 expression depended on the microenvironment (Pérez-Sala and Lamas, 2001).…”
Section: Discussionmentioning
confidence: 73%